Morality and Utility - Narveson, Jan (Johns Hopkins University Press, 2019)
Originally published in 1967. In the past half-century, Utilitarianism has fallen out of favor among professional philosophers, except in such "amended" forms as "Ideal" and "Rule" Utilitarianism. Professor Narveson contends that amendments and qualifications are unnecessary and misguided, and that a careful interpretation and application of the original theory, as advocated by Bentham, the Mills, and Sidgwick, obviates any need for modification. Drawing on the analytical work of such influential recent thinkers as Stevenson, Toulmin, Hare, Nowell-Smith, and Baier, the author attempts to draw a more careful and detailed picture than has previously been offered of the logical status and workings of the Principle of Utility. He then turns to the traditional objections to the theory as developed by such respected thinkers as Ross, Frankena, Hart, and Rawls and attempts to show how Utilitarianism can account for our undoubted obligations in the areas of punishment, promising, distributive justice, and the other principal moral convictions of mankind. He contends that the Principle of Utility implies whatever is recognized to be clearly true in these convictions and that it leaves room to doubt whatever is doubtful in them. Narveson concludes with a rationally forceful proof of the Principle of Utility. In the course of this argument, which draws on the most widely accepted recent findings in analytical ethics, Narveson discovers an essential identity between the ethical outlooks of Kant and of Mill, which are traditionally held to be antithetical. Both thinkers, he shows, center on the principle that the interests of others are to be regarded as equal in value to one's own. A new view of Mill's celebrated "proof of utilitarianism" is developed in the course of the discussion.